Domy z "chceń i snów uwite". Motyw domu w poezji Janusza Artura Ihnatowicza - Jakubowska-Ożóg, Alicja (Tematy i Konteksty, 2011)
The aim of the article is to discuss the motifs of home and house in the selected literary works by one of the Polish émigrés associated with the London poetical group known as „Kontynenty”. The motifs serve an important purpose in the poetical biography of Ihnatowicz – house as a physical object can be found only in descriptions of his memories: an abode ruined by time and history. However, among his writings one can also find many expressions of homesickness denoted by a wish for a safe place to live. The article undertakes the attempt to situate the motifs in the context of the philosophy of Martin Heidegger, who perceives human thoughts and language as shelters for places physically lost.